Human development in Vietnam: Realities and prospects - DUYEN, DR. NGUYEN THI THUY; TRI, DR. NGUYEN MINH (The journal of contemporary issues in business and government, 2021)
Humans are both the target and the driving force behind the socio-economic development of each country in all times. Therefore, during the process of leading the revolution, Vietnam always considers people as the most precious capital, the goal and the driving force of the revolution, as the decisive factor for the success or failure of the revolution, especially in the process of international integration with a new comprehensive and profound awareness of both theory and practice in all fields, awareness of the position and role of human is also becoming more complete and profound. Vietnam always puts people at the center of the development process, that is the object, target and driving force of all socio-economic activities. Currently, Vietnam has become a low-middle income country and has reaped many achievements in human development. However, the reality still has many limitations and weaknesses, requiring the Government to have appropriate solutions and policies to promote human development that meet the requirements of sustainable development in Vietnam in the coming time.